PEMASANGAN LUBANG RESAPAN BIOPORI DI RW 20, DESA CIANGSANA, KABUPATEN BOGOR - Winarni Winarni; Ramadhani Yanidar; Olivia Seanders (Universitas Trisakti, 2022)
Cantik eco-friendly village (KRL Cantik) - RW 20, in Ciangsana Village, Bogor Regency, had a target to install 1000 biopore infiltration holes (LRBs) to increase the groundwater recharge. Supporting this program, the PkM team of Environmental Engineering Study Program provided assistance to the KRL Cantik Management with the aim of increasing the insight and understanding of the RW 20 residents regarding water conservation and the installment of LRBs in accordance to technical requirements that will avoid the groundwater contamination. The methods used are (i) providing educational materials to the representatives of RW 20 residents through direct explanationa and leaflets regarding rainwater runoff, groundwater recharge, and the LRBs benefits, (ii) providing training for LRB installation in site i.e the Balai RW 20, and (iii) providing a video of activities to disseminate the installment of 1000 LRBs by KRL Cantik Management to all residents of RW20. The result of this activity is an increase in residents' understanding of the implications of installing LRB in their respective homes to the increasing ground water capacity.